Simulation-Length Requirements in the Loads Analysis of Offshore Floating Wind Turbines: Preprint - Haid, L.; Stewart, G.; Jonkman, J.; Robertson, A.; Lackner, M.; Matha, D. (National Renewable Energy Laboratory (U.S.), 2013)
The goal of this paper is to examine the appropriate length of a floating offshore wind turbine (FOWT) simulation - a fundamental question that needs to be answered to develop design requirements. To examine this issue, a loads analysis of an example FOWT was performed in FAST with varying simulation lengths. The offshore wind system used was the OC3-Hywind spar buoy, which was developed for use in the International Energy Agency Code Comparison Collaborative Project and supports NREL's offshore 5-megawatt baseline turbine. Realistic metocean data from the National Oceanic and Atmospheric Administration and repeated periodic wind files were used to excite the structure. The results of the analysis clearly show that loads do not increase for longer simulations. In regards to fatigue, a sensitivity analysis shows that the procedure used for counting half cycles is more important than the simulation length itself. Based on these results, neither the simulation length nor the periodic wind files affect response statistics and loads for FOWTs (at least for the spar studied here); a result in contrast to the offshore oil and gas industry, where running simulations of at least 3 hours in length is common practice.